Kaizen event fieldbook : foundation, framework, and standard work for effective events - Hamel, Mark R. (Society Of Manufacturing Engineers, 2010)
Kaizen event effectiveness is a prerequisite for lean transformation success. It provides the necessary transformational jump-start, momentum, organizational learning and engagement, and sustainable, step-function improvements. This book is suitable for lean leaders in industry and for use at various stage within the lean implementation journey.
Keywords: Production management.; Manufacturing processes.; elektronické knihy; electronic books